OS10.8.A The effectiveness of antiepileptic drug duotherapies in glioma patients: a multicenter observational cohort study. (9th September 2021) - van der Meer, P B; Dirven, L; Fiocco, M; Vos, M; Kouwenhoven, M C M; van den Bent, M J; Taphoorn, M J B; Koekkoek, J A F
Abstract: BACKGROUND: About 30% of glioma patients need an add-on antiepileptic drug (AED) due to uncontrolled seizures on AED monotherapy. This study aimed to determine whether levetiracetam combined with valproic acid (LEV+VPA), a commonly prescribed duotherapy, is more effective than other duotherapy combinations including either LEV or VPA in glioma patients. MATERIAL AND METHODS: In this multicenter retrospective observational cohort study, treatment failure (i.e. replacement by or addition of a new AED, or withdrawal of an AED) for any reason was the primary outcome. Secondary outcomes included: 1) treatment failure due to uncontrolled seizures; and 2) treatment failure due to adverse effects. Time to treatment failure was defined as the time from the start of AED duotherapy until the time of treatment failure. Multivariable Cox proportional hazard models were estimated to study the association between risk factors and treatment failure. The maximum duration of follow-up was 36 months. RESULTS: A total of 1435 patients were treated with first-line monotherapy LEV or VPA, of which 355 patients received AED duotherapy after they had treatment failure due to uncontrolled seizures on monotherapy. LEV+VPA was prescribed in 66% (236/355) and other AED duotherapy combinations including LEV or VPA in 34% (119/355) of patients. Patients using other duotherapy versus LEV+VPA had higher risk of treatment failure for any reason (cause-specific hazard ratio [csHR]=1.50 [95%CI=1.07–2.12], p=0.020), treatment failure due to uncontrolled seizures (csHR=1.73 [95%CI=1.10–2.73], p=0.018). There were no differences in failure due to adverse effects (csHR=0.88 [95%CI=0.47–1.67]), p=0.703) between the two groups. CONCLUSION: This observational cohort study suggests that LEV+VPA has better efficacy than other AED combinations. Similar toxicities were experienced in the two groups.